Detection of extended spectrum β-lactamase (ESBLA), screening of AmpC β-lactamase and detection of CTX-M and aacA-aphD genes among the multidrug resistant bacteria found in two tertiary hospitals of Dhaka city - Sultana, Sarmin (BRAC University, 2018)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Biotechnology, 2017.